Formulation of heat resistant paint from palm oil based resin by using nano-silica particles - Basir, Ahmed; Nadia Suhaila, Muhammad Asyraf Anbalagan; Beg, M. D. H.; R. M., Yunus; Arman, Abdullah (IOP Publishing, 2020)
Paint is the main choices of coatings for various materials, machinery and buildings. Paints formulated from renewable resources and non-toxic chemicals are in demand. The Objective of this study is to prepare and characterize heat resistant paint from palm oil based resin by using nano-silica particles. Palm oil based paint was formulated using resin prepared from cooking oil waste, varied amount of nano-ceramics particles and fixed amount of pigment. Painted samples of aluminium sheet were prepared from formulated paint, cured oven heating method. Heat resistance and corrosion resistance were performed. Sample containing 0.6% silica showed best performance under heat no visible cracks even at 140 oC. Tafel plot shows corrosion resistance with Ecorr -0.91479 V, Icorr 3.2X10-6 A, Corrosion rate 0.0328216 mmy. The best formulation of paint can be benefited in many areas such as industrial paint industry, household appliances that required high thermal resistant and eco-friendly paint.